Music Stand, Golden Gate Park (Edward. H. Mitchell)
On verso: San Francisco has subscribed $7,500,000 to the Exposition Treasury. The State Legislature has made possible $10,000,000 more, that is $5,000,000 by the state & $5,000,000 by the municipality of San Francisco-$17,500,000 in all. Get your Congressman to work and vote for San Francisco 1915.